2020
DOI: 10.7554/elife.56571
|View full text |Cite
|
Sign up to set email alerts
|

The Mla pathway in Acinetobacter baumannii has no demonstrable role in anterograde lipid transport

Abstract: The asymmetric outer membrane (OM) of Gram-negative bacteria functions as a selective permeability barrier to the environment. Perturbations to OM lipid asymmetry sensitize the cell to antibiotics. As such, mechanisms involved in lipid asymmetry are fundamental to our understanding of OM lipid homeostasis. One such mechanism, the Maintenance of lipid asymmetry (Mla) pathway has been proposed to extract mislocalized glycerophospholipids from the outer leaflet of the OM and return them to the inner membrane (IM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 59 publications
(126 reference statements)
3
40
3
Order By: Relevance
“…It should be emphasized that the structural studies reported here support an anteretrograde direction for lipid transport, as supported by our previous biochemical data in A. baumannii (19) as well as other studies in E. coli (11, 19, 20). Nonetheless, other assays point towards a retrograde directionality (18, 21), and the current structures do not conclusively preclude this. Further structural analyses, in particular in complex with the periplasmic carrier MlaC, will be required to definitely resolve this controversy.…”
Section: Discussioncontrasting
confidence: 62%
“…It should be emphasized that the structural studies reported here support an anteretrograde direction for lipid transport, as supported by our previous biochemical data in A. baumannii (19) as well as other studies in E. coli (11, 19, 20). Nonetheless, other assays point towards a retrograde directionality (18, 21), and the current structures do not conclusively preclude this. Further structural analyses, in particular in complex with the periplasmic carrier MlaC, will be required to definitely resolve this controversy.…”
Section: Discussioncontrasting
confidence: 62%
“…It should be emphasized that the structural studies reported here favour an anteretrograde direction for lipid transport by structure similarity, as supported by our previous biochemical data in A. baumannii 21 as well as other studies on E. coli 12 , 19 , 21 . Nonetheless, other assays point towards a retrograde directionality 20 , 23 , and the current structures do not conclusively preclude this. Further structural analyses, in particular in complex with the periplasmic carrier MlaC, will be required to resolve this controversy definitively.…”
Section: Discussioncontrasting
confidence: 58%
“…Despite the tendency of MlaF 2 E 2 D 6 B 2 to facilitate the spontaneous anterograde flow of phospholipids 8,9 , the MlaA channel is not designed to deliver phospholipids into the inner leaflet of the outer membrane; instead, it is meant to extract them from the external leaflet 10 . Indeed, the dominant negative mlaA* mutation reverses the protein's normal function by allowing phospholipids to flow directly into the external leaflet 11 .…”
Section: Russell E Bishopmentioning
confidence: 99%
“…Three new papers report cryo-EM structures of nearly full-length human SARM1 (refs. [9][10][11] ), representing another major breakthrough in this exciting area of research. These structures define an inactive state of SARM1 and reveal a mechanism by which its NADase activity is turned off.…”
Section: Competing Interestsmentioning
confidence: 99%